Investigation of Stimulated Brillouin Scattering effect on different modulation formats - Moghaddasi, Majid; Seyedzadeh, Saleh; Shokri, Shervin; Hassan, Mazen Radhe; Shamel, Kaveh; Ahmad Anas, Siti Barirah (Maxwell Science Publication, 2014)
In this study, the impact of Stimulated Brillouin Scattering (SBS) and effective core area and the Brillouin gain coefficient on On-Off Key (OOK) and phase modulation formats is investigated. In comparison with OOK formats, Return to Zero-Differential Phase Shift Keying (RZ-DPSK) revealed more robustness against the SBS effect with regards to jitter. The generated jitter due to power increment from 0 to 6 dBm was measured. The results show 0.1232, 0.1054, 0.0683 and 0.0544 bit period jitter for NRZ-OOK, RZ-OOK 0.5, NRZ-DPSK and RZ DPSK respectively. Furthermore, it is shown that SBS effect changes the behavior of system with regards to bit rate variation. It is shown that lower bit rate, does not guarantee higher performance. For instance, while the log BER at 2 Gb/sec is -11 for RZ-OOK 0.5, -9 for CSRZ,-10 for NRZ-DPSK and -16 for RZ-DPSK, at 8 Gb/sec they hit a peak with -16, -20, -21 and -36, respectively.